Pengembangan E-LKPD Berbasis Multimedia Menggunakan Zep Quiz pada Materi Jurnal Penyesuaian untuk Meningkatkan Keterlibatan Belajar Siswa: Development of Multimedia-Based Electronic Student Worksheets (E-LKPD) Using Zep Quiz on the Topic of Adjusting Entries to Enhance Student Learning Engagement - Ismiyatinur Azizah; Rochanda Wiradinata; Rusdiyana Rusdiyana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Learning about adjusting entries in Vocational High Schools (SMK) requires the ability to identify accounts, calculate amounts, and construct accurate journal entries. A needs analysis revealed that students struggle to grasp adjustment procedures and require repeated practice accompanied by immediate feedback. Conventional teaching materials tend to render students passive and disengaged. Consequently, there is a need for interactive digital media that integrates content, practice exercises, and evaluation. A multimedia-based Electronic Student Worksheet (E-LKPD) integrated with the "Zep Quiz" digital quiz platform offers a unified learning experience; it provides immediate feedback and incorporates gamification elements to boost student engagement. The study employed the Research and Development (R&D) method using the ADDIE model. The stages of Analysis, Design, Development, Implementation, and Evaluation were carried out systematically to produce a valid product. Subject matter, media, and pedagogical experts conducted validation. Data were collected via validation sheets and response questionnaires, then analyzed using descriptive quantitative methods. Validation results demonstrated a very high level of feasibility: 88.00% from subject matter experts, 84.00% from media experts, and 84.00% regarding pedagogical aspects, yielding an overall average of 85.33% (highly feasible). Student responses yielded an average score of 3.30 (highly feasible), with the ease of understanding the material and the engaging nature of the quizzes cited as key strengths. The multimedia-based E-LKPD utilizing Zep Quiz was deemed highly feasible and well-received, making it a viable, innovative learning medium to enhance student engagement and comprehension regarding adjusting entries.